Sex-specific differences in the association of dietary riboflavin intake with depression and suicidal ideation - Chu, Haorui; Liu, Dongyu; Peng, Wei; Qiao, Tianci (Frontiers in Nutrition, 2025)
Background:Attention is increasingly focused on the relationship between dietary micronutrients and affective disorders. Currently, the association of riboflavin intake with depression and suicidal ideation is controversial. Therefore, the present study utilized a large population-based database to explore these relationships.MethodsWe included 29,466 participants. The study data was weighted for analysis. The associations of dietary riboflavin intake with depression and suicidal ideation were examined using logistic regression models. To elucidate the dose-response relationship of dietary riboflavin intake with outcomes, we used restricted cubic splines. Recursive methods were utilized to identify the inflection point. Subsequently, stratified analyses were conducted to investigate differences across subgroups.ResultsAfter adjusting for all confounding factors, the ORs (95% CIs) for the association of dietary riboflavin intake with depression and suicidal ideation were 1.02 (0.93, 1.11) and 1.09 (0.93, 1.28), with no statistical significance. The restricted cubic splines indicated non-linear associations, and the relationship of dietary riboflavin intake with depression was inverse only before the inflection point (1.44 mg/day). In the relationship with suicidal ideation, significant association was found both before and after the inflection point (1.42 mg/day). Furthermore, sex-specific subgroup differences were found.ConclusionsIn this large-sample study, the non-linear association of dietary riboflavin intake with depression and suicidal ideation was found. Furthermore, differences in this relationship based on sex were observed.